IMPROVING COORDINATION AND COLLABORATION FOR MULTI-STAKEHOLDER PARTICIPATION TO ACHIEVE - Indrawati, Sri Wahyu; Rohana, Rohana; Yusanti, Indah Anggraini; Permatasari, Nuryanti; Padillah, Padillah; Sari, Syska Purnama (MAJU : Indonesian Journal of Community Empowerment, 2024)
The document describes an international community service program that focuses on multi-stakeholder participation in achieving Development Goals. Sustainable for Indonesia and Malaysia. SDGs represent the global agenda for sustainable development. To achieve this goal requires collaboration between government, the private sector, civil society organizations and the community. Both Indonesia and Malaysia face challenges such as poverty, inequality and environmental degradation in their efforts to achieve the SDGs.